Level of Motivation and Adoption of Innovation at Pig Farming in Southwest Sumba Regency - H. U. Padu; A. A. Nalle; O. H. Nono; M. F. Lalus; S. Sembiring (Jurnal Sain Peternakan Indonesia, 2022)
The development of pig farming aims to support the economy of the people in the Southwest Sumba Regency. Pigs in this area have a very high cultural value, so they have promising potential and prospects in the future. The problem is that the maintenance system is still semi-extensive and tends to be traditional. This situation can be related to the motive in trying and efforts to adopt an innovation. This study aimed to analyze the level of motivation and the factors that influence the adoption of innovation in raising pigs. The research method used a survey method with direct observation in the field. They are determining the area using the multistage cluster random sampling method obtained from sample sub-districts, namely Tambolaka District (Tambolaka City and Wee Londa) and South Wewewa District (Tena Teke Village and Delo). The research material was 120 pig farmers taken by purposive random sampling. The measured variables include the motivation to raise livestock using a Likert scale and factors influencing innovation adoption using multiple linear regression tests. The software used is Eviews 10. The study results show that: 1) Most of the pig breeders in Southwest Sumba Regency are based on high economic, social, and entertainment motives in pig farming. 2) The regression results show that the variables that have a significant effect on the level of adoption with a prob value below the significant level of 0.05 are the variables of motivation and access to information. While the variables that have no significant effect on the level of innovation adoption with a prob value above the significant level of 0.05 are the variables of age, education level, family dependents, livestock experience, number of livestock, and accessibility. This study concludes that business motives and adoption of innovations affect the success or failure of pig-rearing businesses in the Southwest Sumba district.